Keadilan Restoratif dan Mediasi Penal Dalam Tindak Pidana Ringan - Kristiyadi, Kristiyadi; Setyawan, Vincentius Patria (Universitas Muhammadiyah Palembang, 2022)
The objective of punishment has evolved from the philosophy of retaliation (retributive) to justice-based remedies (restorative justice) (restorative justice). Restorative justice is a sentencing purpose that is oriented towards the recovery of victims of criminal crimes. In addition to focusing on victims, restorative justice also tries to seek the best solution for crime victims, and perpetrators, as well as the families of the perpetrators and the families of the victims. One of the strategies utilized to accomplish restorative justice is criminal mediation. This article will explain about prison mediation as an alternate settlement of small crimes. The method utilized in authoring this work is a normative legal research method comprising a conceptual approach and a statutory approach. The results of this study are the need for written, clear and firm rules regarding penal mediation, and the application of penal mediation in minor crimes will bring benefits, namely preventing perpetrators from the negative impact of punishment, recovering victims, and supporting the realization of the principle of simplicity, speed and low cost. in the criminal justice process.Keywords: Restorative Justice; Penal Mediation; Criminal Cases